Analisa Kandungan Logam Berat Krom pada Air Sumur Menggunakan Spektrofotometri - Triastuti, Warlinda Eka; Agustiani, Elly; Sampurno, Ade Citra Oktaviana Elok; Fitria, Yustia Dwi; Fauziyah, Hanifah; Rahma, Sunia; Rudianto, Anaral Al Ardhi; Amalia, Firda; Damayanti, Avisa (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Clean water has many uses in human daily life. The quality of clean water can be seen from three aspects: chemical, physical, and biological. Chromium (VI) or Cr (VI) is one type of heavy metal that can be harmful to human health if it is present in water because it is carcinogenic. This research will determine the level of chromium in well water samples in the Kalipecabean, Keputih, Kapas Madya, Nginden, and Madura areas using UV-Vis spectrophotometry and compare it with the Regulation of the Minister of Health of the Republic of Indonesia Number: 32/MENKES/PER/2017. The initial stage of the experiment includes the preparation of reagent solutions, followed by the calibration of the instrument and the preparation of a standard curve by making standard solutions with concentrations of 1, 2, 3, 4, and 5 ppm. The standard solutions are then tested for their absorbance using a spectrophotometer. The final stage is adding reagents to the water samples and measuring their absorbance using a spectrophotometer. From the results of the study, it was found that the levels of chromium in the well water samples in the Kalipecabean, Keputih, Kapas Madya, Nginden, and Madura areas are 0.004 ppm, 0.005 ppm, 0.005 ppm, 0.002 ppm, and 0.003 ppm, respectively. The experimental results show that the level of chromium contained in the well water is relatively low and still meets the maximum chromium content level in water according to the Regulation of the Minister of Health of the Republic of Indonesia Number: 32/MENKES/PER/2017.